Scientific contribution of Turkey in prostate literature. Where are we? Where are we going? - Selahattin Çalışkan; Mustafa Sungur (Journal of Oncological Sciences)
Prostate cancer is a common malignancy in the world. The established risk factors are increasing age, race and family history. The incidence of prostate cancer is low in Asia, but the overall age-adjusted incidence rate of PCa was reported as 35/100,000 from years of 2008 to 2009 in Turkey. The aim of the study is to investigate the articles from Turkey about prostate cancer for ten years period. The data from the Institute for Scientific Information Web of Science was reviewed and ‘prostate adenocarcinoma’ in the title was searched in each year from 2006 to 2015. The article, review and letter were selected. Number of articles from Turkey and world was recorded and localization of the top ten countries were noted. There were 28,714 articles between 2006 and 2015 years. The articles increased from 11,998 to 16,716 in last 5 years. In Turkey; the articles was 120 in first 5 year and increased to 205 in the last 5 years. The percentage of increases was 39.3 and 70.8% in the world and Turkey. Ranking to the countries according to the article numbers; Turkey was between 17–23 and 16–27 in first and second five years. The number of the countries whom published prostate cancer articles reached to 89 in ten years. The number of the articles is increased during the years. When we think the nüfüs of the country and number of the academicians, the number of the articles would be more than today. The urologists must work more than last to improve the Turkish scientific localization. The clinical chefs of the university and training hospitals can organize well designed clinical studies and Turkish Association of Urology and Oncology promote the clinical studies, we can publish more and more studies.